Peningkatan Pemahaman Konsep Makna Lambang Negara Menggunakan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Shadow Puppets Pada Siswa Kelas III SDN Gerih 4 Kabupaten Ngawi - kusumawardhani, intan; Apriandi, Davi; Solikah; Sukarni (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to increase understanding of the concept of the meaning of the state symbol using a problem-based learning model assisted by shadow puppets media. The research method uses Classroom Action Research (PTK) with the Kemmis and Mc Taggart PTK models and approaches to quantitative and qualitative data consisting of two cycles. Each cycle consists of planning, implementing, observing, and reflecting. The subjects of this study were class III students at SDN Gerih 4 for the 2022/2023 academic year. Data collection techniques are observation, interviews, documentation and evaluation test questions. The results of the study show that the use of problem-based learning models assisted by shadow puppets media can improve understanding of the concept of the meaning of national symbols. This is shown by the percentage of completeness in cycle I of 78.57% with an average value of 77.14, an increase in the percentage of completeness in cycle II of 92.85% with an average value of 82.85.